Computational underpinnings for the dimerization of para-aminothiophenol to dimercaptoazobenzene on copper surface - Bhadoria P.; Ramanathan V. (My University, 2025)
The chemical transformation of PATP (para-aminothiophenol) adsorbed on copper to its dimer DMAB (p, p’-dimercaptoazobenzene) upon laser irradiation was computationally studied using the generalized gradient approximation for exchange–correlation functionals PW91PW91. Copper atoms were treated by relativistic effective core potentials (RECP) with (LANL2DZ) and for C, H, N, and S atoms 6–311 + G(d,p) basis set was used. The simulated SERS (surface enhanced Raman spectroscopy) spectrum of DMAB on copper cluster was observed in perfect match with the experimentally observed SERS of PATP on copper. Thus the enhanced signals observed in SERS of PATP were not the enhanced b2 modes of PATP but these were the ag modes of DMAB, which is formed due to the surface catalytic coupling reaction. © 2023 Elsevier B.V.